Analisis Kondisi Rumah, Sosial Ekonomi dan Perilaku sebagai Faktor Risiko Kejadian Frambusia di Kota Jayapura Tahun 2007 - R. Indra Boedisusanto, Fajar Waskito, Haripurnomo Kushadiwijaya (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Yaws is caused by spiral bacillus called treponema perteneu. It is a human infectious disease which commonly attacks skin and bones. The prevalence of yaws in Indonesia was less than 1 per 10,000 people but there were places with high prevalence such as Provinces of West Papua, Papua, South East of Sulawesi, Nusa Tenggara Timur and Maluku. The prevalence of yaws in Jayapura Municipality in 2007 was 5.4 per 10,000 people.Objective: To identify risk factors of house condition, social economic factors and behavioral factors of the occurence of yaws at Jayapura Municipality.Method: The study was observational with case control study design. Sample of the study consisted of 84 cases and 84 control subjects. Data were analyzed using computer with 2 x 2 tables and multiple logistic regression tests at 95% significant level.Result: Multivariable analysis showed that three variables were significant risk factors for the occurence of yaws: house condition (occupancy density, OR=2,5, availability of clean water, OR=5.9), and behavior (taking a bath, OR=3.8).Conclusion: Factors of house condition (occupancy density, availability of clean water), social economy (knowledge) and behavior (taking a bath) are dominant risk factors for the occurence hence prevalence of yaws at Jayapura Municipality.Keywords: Yaws, risk factors, Jayapura Municipality